Evaluation of River Water Quality at Bridge Construction Site and Preservation of the Trans Papua Mameh-Bintuni Road West Papua Province - Marhan Manaf; Suhaemi Suhaemi; Tutik Handayani; Bayu Pranata (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The construction of bridges and the Trans Papua Mameh-Bintuni road section of West Papua Province crosses rivers (Mothy-I Bridge), (Mothy-II Bridge), and (Yuki-II Bridge). The impact of this development is estimated to affect a decrease in river water quality and pollution. River water quality criteria are determined based on the pollution indicator. Water quality samples were taken from rivers directly affected by bridge construction activities and the Trans Papua Mameh-Bintuni road preservation. Water quality parameters and river water sampling refer to SNI 6989.57:2008. Water sampling was carried out after the construction activities were completed. The results showed that the water quality in the three rivers met the class II river water quality standards according to Government Regulation No. 22 of 2021. The Pollution Index of rivers (Mothy-I Bridge), rivers (Mothy II Bridge), and rivers (Yuki Bridge II) each has a Pollution Index value of 0.769; 0.816; and 0.770. This value describes the water quality in the three rivers in the excellent category, qualify environmental quality standards. Biological, chemical and physical indicators are in the natural concentration value, thus the bridge construction activities and the preservation of the Mameh-Bintuni road in West Papua Province that have been carried out do not have a negative impact on changes in river water quality.